Admission hypocalcemia in pediatric major trauma patients—An uncommon phenomenon associated with an increased need for urgent blood transfusion. Issue 7 (31st May 2022) - Epstein, Danny; Ben Lulu, Hen; Raz, Aeyal; Bahouth, Hany
Abstract: Background: Hemorrhage is a leading cause of death among children. Recent data from adult trauma suggests that early, transfusion‐unrelated, hypocalcemia is common and that it is associated with an increased need for blood transfusion, mortality, and coagulopathy. The objectives of this study are to evaluate the prevalence of admission hypocalcemia in severely injured children and its correlation with urgent blood transfusion. Study Design and Methods: This is a retrospective cohort study of all severely injured (Injury Severity Score [ISS] > 15) pediatric (<18 years) trauma patients admitted to Rambam Health Care Campus, Israel between 2012 and 2020. We excluded patients transferred from other facilities and those who received blood before determining calcium levels. Severe hypocalcemia was defined as ionized calcium (Ca ++ ) < 1.0 mmol/L and mild hypocalcemia as 1.0 mmol/L ≤ Ca ++ < 1.1 mmol/L. The primary outcome was urgent blood transfusion (transfusion in the emergency department [ED]). Results: Six hundred seventy‐three severely injured children were admitted from the field. Ca ++ levels were determined before blood transfusion in 457 patients. Severe hypocalcemia was found in three patients (0.7%) and mild hypocalcemia in additional 21 patients (4.6%). Hypocalcemic patients required more urgent blood transfusion (29.2% vs. 6.5%, p < .001) and had higher ISS (29 [interquartile range, IQR: 22–35] vs. 25 [IQR: 19–34], p = .05). Multivariable logistic regression analysis identified Ca ++ < 1.1 mmol/L as an independent predictor of the need for blood transfusion, odds ratio 5.44 (95% confidence interval 1.44–20.58), p = .01. Discussion: Contrary to adults, admission hypocalcemia is uncommon in severely injured children. However, it may be associated with an increased risk of blood transfusion in the ED.